The Influence of The Principal's Leadership Style and School Culture On Teacher Performance Mediated By Work Motivation - Febriana Kristin Marjono; Andreas Heryjanto (Jurnal Indonesia Sosial Sains, 2023)
The purpose of this study is to examine the Influence of School Principal's Leadership Style and School Culture on Teacher Performance Mediated by Work Motivation in XYZ School, Lampung, Indonesia. This study is quantitative research with 142 teachers’ population at XYZ School, Lampung, Indonesia. The respondent criteria include teachers who have been teaching for a minimum of 6 months, based on the teacher data available in May 2023 in XYZ School, Lampung, Indonesia, with no restrictions on gender and age. Based on the Slovin sample size calculation above, the sample size used in this study was 105 respondents. The data analysis technique used descriptive analysis of Partial Least Square Structural Equation Modeling (PLS-SEM) to measure the relationship between variables with the assistance of SmartPLS software. The research findings indicate that the variables of principal’s leadership style, school culture, and work motivation have a positive and significant influence on teacher performance. In addition, the principal's leadership style has a positive and significant effect on teacher performance, school culture has a positive and significant effect on teacher performance, the principal's leadership style has a positive and significant effect on work motivation, school culture has a positive and significant effect on work motivation, work motivation has a positive and significant effect on teacher performance, the principal's leadership style has a positive and significant effect on teacher performance mediated by work motivation, and school culture has a positive and significant effect on teacher performance mediated by work motivation